2022
DOI: 10.1093/mnras/stac602
|View full text |Cite
|
Sign up to set email alerts
|

Birth cluster simulations of planetary systems with multiple super-Earths: initial conditions for white dwarf pollution drivers

Abstract: Previous investigations have revealed that eccentric super-Earths represent a class of planets which are particularly effective at transporting minor bodies towards white dwarfs and subsequently polluting their atmospheres with observable chemical signatures. However, the lack of discoveries of these planets beyond a few astronomical units from their host stars prompts a better understanding of their orbital architectures from their nascent birth cluster. Here, we perform stellar cluster simulations of 3-plane… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…Therefore, the change in secular modes will be dominated by the changes to the semi-major axis of the outermost planet. Additionally, numerical studies involving stellar flybys have shown that changes to the architecture of a planetary system correlates with the number of planets and the initial semi-major axis of the outermost planet (Stock et al 2022). Note that we now have a straightforward scaling relationship that goes from encounter parameters (m , b , v∞) to |∆gj/gj|.…”
Section: Two Planetsmentioning
confidence: 93%
“…Therefore, the change in secular modes will be dominated by the changes to the semi-major axis of the outermost planet. Additionally, numerical studies involving stellar flybys have shown that changes to the architecture of a planetary system correlates with the number of planets and the initial semi-major axis of the outermost planet (Stock et al 2022). Note that we now have a straightforward scaling relationship that goes from encounter parameters (m , b , v∞) to |∆gj/gj|.…”
Section: Two Planetsmentioning
confidence: 93%
“…A growing number of studies are trying to connect the influence of clustered star-forming environment with the architectures of the resulting planet populations (e.g., [136][137][138][139][140][141][142][143]). Many of these focus on dynamical interactions that sculpt already formed planetary systems.…”
Section: Cluster Impact On Disksmentioning
confidence: 99%
“…Dynamical models indicate that post-main-sequence evolution of planetary systems and the subsequent evolution into a white dwarf may trigger orbital instabilities (Debes & Sigurdsson 2002;Veras & Veras 2021). Moreover, the subsequent chaotic evolution may disrupt previously stable planetary systems (Veras & Gansicke 2015;Mustill et al 2018;Zink et al 2020;Stock et al 2022). Side effects of these instabilities such as high-eccentricity scattering and collisions between planets or planetary material and the white dwarf may partially explain the observed pollution (Veras et al 2013;Veras & Fuller 2019).…”
Section: Introductionmentioning
confidence: 99%